2019
DOI: 10.14712/23366052.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Maximal oxygen uptake and concentric isokinetic muscle strength in pubertal football trained and untrained boys of the same biological age

Abstract: The purpose of the present study was to examine the effects of long term (prolonged) football training on maximal oxygen uptake (® VO 2) and isokinetic muscle strength in young football players and untrained boys of the same biological age. Twenty football competitive boys (mean age 14 ± 0 yrs; height 165.5 ± 8.5 cm; weight 59.9 ± 9.5 kg; years of training 7 ± 3) and eighteen untrained school boys (mean age 14 ± 0; height 168.22 ± 10.46 cm; weight 59.3 ± 9.9 kg) of the same biological age volunteered to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The objective determination of this association supported the notion that engaging children in specific sport activities, such as football, track and field, swimming, and basketball, increases their levels of cardiorespiratory fitness. These findings broadly support the results of other studies [ 22 , 23 , 24 , 25 ]. Furthermore, higher training frequency had an additive effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The objective determination of this association supported the notion that engaging children in specific sport activities, such as football, track and field, swimming, and basketball, increases their levels of cardiorespiratory fitness. These findings broadly support the results of other studies [ 22 , 23 , 24 , 25 ]. Furthermore, higher training frequency had an additive effect.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have indicated that physical activity is relatively well-correlated with aerobic capacity [ 17 , 18 , 19 , 20 ]. Moreover, only a few studies have taken into account the relationship between different sports activities and VO 2 max [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seven cases were on the left side, and 13 were on the right--side. 3 There were 11 males and 9 females. The average age was 25.3 years, the height was 166.4±5.0cm, the weight was 64.7±4.8kg, and the disease course was 28.6±18.3 months.…”
Section: Research Objectmentioning
confidence: 99%